PERAN ORANG TUA DALAM MENDIDIK ANAK SEJAK DINI SECARA ISLAMI DI ERA MILENIAL 4.0 - Ida Latifatul Umroh (TA'LIM : Jurnal Studi Pendidikan Islam, 2019)
Children are the desire of every married couple. Children given by Allah to His servants will be held accountable in the afterlife. Parents' obligations to their children do not only meet their physical needs. But the most important thing is to provide him with education, especially religious education. And parental obligations in providing education must begin early. Family education plays an important role as the foundation of further education, especially to face the challenges of education in the 4.0 era. The study in this paper uses the method of library study, which aims to determine the role of parents in educating children from an early Islamic age in the 4.0 era. The results of this study are parents have a role as forming the positive character of children from an early age. In shaping the positive character of children in the 4.0 era, parents must continue to learn about ways to educate children. The things that can be done by parents in educating children in the 4.0 era are: maintaining good communication, knowing trends loved by children so they know how to filter them, setting aside free time for children, being gentle with children, digging information about children's activities, equip children with a strong religious education, pray for children.